Biphasic redox chemistry of alpha-tocopherol: Evidence for electrochemically induced hydrolysis and dimerization on the surface of and within femtolitre droplets immobilized onto graphite electrodes - Wain, A; Wadhawan, J; France, R; Compton, R (2004)
The voltammetric behaviour of α-tocopherol, when immobilized as microdroplets on a basal plane pyrolytic graphite electrode and immersed in aqueous electrolyte is reported. Under these biphasic conditions, the electrochemical oxidation is successfully shown to involve two competing pathways initially involving either one or two electrons, the products of which undergo chemical reactions to form electroactive species. One pathway generates a quinone via ring opening hydrolysis at the electrode |α-TOH| aqueous electrolyte three-phase boundary of the femtolitre volume droplets which undergoes reduction on the reverse sweep. The other produces a dimer, via the coupling of α-tocopherol derived radicals, which can be oxidized further to produce cyclized spiro-dimer. Both pathways involve proton expulsion from the redox liquid phase.